2011
DOI: 10.1002/jsfa.4569
|View full text |Cite
|
Sign up to set email alerts
|

Sensory profiles of breast meat from broilers reared in an organic niche production system and conventional standard broilers

Abstract: BACKGROUND: Breast meat from broilers produced in very different production systems may vary considerable in sensory profile, which may affect consumer interests. In this study the aim was to evaluate differences in the sensory profiles of breast meat from five broiler products: two conventional standard products (A and B) and three organic niche genotypes (I657, L40 and K8) reared in an apple orchard.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 28 publications
3
18
0
1
Order By: Relevance
“…The positive correlation between taste and overall liking implies that an increase in meat taste led to increased overall preference of the meat. Concurring with the current results, Horsted et al (2011) reported a significant correlation between overall liking and scores of taste in broiler meat. Further analysis of the organoleptic scores indicated that treatment had an effect on the degree of consumer preference in all organoleptic characteristics (P <0.05) ( Table 9).…”
Section: Resultssupporting
confidence: 89%
“…The positive correlation between taste and overall liking implies that an increase in meat taste led to increased overall preference of the meat. Concurring with the current results, Horsted et al (2011) reported a significant correlation between overall liking and scores of taste in broiler meat. Further analysis of the organoleptic scores indicated that treatment had an effect on the degree of consumer preference in all organoleptic characteristics (P <0.05) ( Table 9).…”
Section: Resultssupporting
confidence: 89%
“…Beef originating from animals administered green forage is characterized by a higher content of linolenic acid and by lower contents of oleic and linoleic acids than the beef produced from animals administered feed concentrates, which eventually affects also the volatiles formed (Elmore et al, 2004). Generally, meat obtained from the organic production system has taste and aroma that are more desirable by consumers (Horsted et al, 2012). In turn, meat of sheep grazing on pastures is rich in terpenes and diterpenoids, whereas that of sheep administered feed mixtures is characterized by a high concentration of γ-lactones.…”
Section: Factors Affecting Changes In Volatile Compoundsmentioning
confidence: 99%
“…In the systems of less intensive production, the slow-growing birds prove well since their lower growth rate and lower body weight are factors facilitating better health status and lesser mortality [Fanatico et al, 2008;Mikulski et al, 2011]. In addition, it is worth emphasizing that in the unconventional rearing systems the birds are reared for a longer period of time, which allows their meat to attain desirable sensory values [Horsted et al, 2012]. Consumers are searching for bioproducts originating from birds that are fed appropriately and allowed to use free ranges and satisfy their natural behaviors [Dawkins et al, 2003;Aksoy et al, 2010].…”
Section: Introductionmentioning
confidence: 99%